Identification of Drug Related Problems (DRPs) in Rheumatoid Arthritis Patients at Palembang City Hospital - Hairun Niza; Sarah Hanifah Az-Zahra Anwar; Sintya Merinda (Universitas Airlangga, 2024)
Background: Rheumatoid arthritis is a chronic systemic inflammatory arthritis disease that affects mainly synovial joints. The incident of RA can lead to the emergence of complications or comorbidities, which then allows patients to receive a variety of therapies that can trigger the incidence of DRPs during the treatment. The prevalence of RA in Indonesia itself in 2018 has reached 7.30%, with the highest percentage occurring in the elderly age group and more prevalent in women. Objective: This study aimed to determine the incidence of DRPs in RA patients in Palembang city hospitals based on the category of DRPs identified as related to drug selection and dose selection problems, as the relationship between demographic factors and the incidence of DRPs. Methods: This research is non-experimental study conducted with a retrospective cross-sectional survey. Data collection was carried out by looking at patient medical record data at X and Y Hospital in Palembang from January 2021 to March 2023. Results: The results showed that the most frequent drps in the drug selection category were drug interactions (72.03%), while in the dose selection category were insufficient dosage regimens (60.74%). The results of bivariate analysis between the incidence of DRPs and gender (p=0.809), age (p=0.879), the number of drugs used (p=0.001), and comorbidities (p=0.089). Conclusion: There is no relationship between demographic factors and comorbidities with the incidence of DRPs, and there is a relationship between the number of drugs and the incidence of DRPs.